If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10(-2x + 7) = -19(x + 1) Reorder the terms: 10(7 + -2x) = -19(x + 1) (7 * 10 + -2x * 10) = -19(x + 1) (70 + -20x) = -19(x + 1) Reorder the terms: 70 + -20x = -19(1 + x) 70 + -20x = (1 * -19 + x * -19) 70 + -20x = (-19 + -19x) Solving 70 + -20x = -19 + -19x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '19x' to each side of the equation. 70 + -20x + 19x = -19 + -19x + 19x Combine like terms: -20x + 19x = -1x 70 + -1x = -19 + -19x + 19x Combine like terms: -19x + 19x = 0 70 + -1x = -19 + 0 70 + -1x = -19 Add '-70' to each side of the equation. 70 + -70 + -1x = -19 + -70 Combine like terms: 70 + -70 = 0 0 + -1x = -19 + -70 -1x = -19 + -70 Combine like terms: -19 + -70 = -89 -1x = -89 Divide each side by '-1'. x = 89 Simplifying x = 89
| 9x(x^3+5)= | | 9y-4-6y=2[y+1]-5 | | A=210+20(h-7) | | -8-10+8r=-2+10 | | 4p+3-2p=27 | | f+9=21 | | -3x+5x-19=19 | | 9y-4-6y=2[y+1] | | 25-30x=65-20x | | -3-2x=6x+15 | | 17=h-8 | | -9+4(x-2)=15 | | 3-4-9= | | 30=-6(-3c-8) | | 11x-(6-5)=40 | | y=3x^2+18x+32 | | 23x-13y=-3 | | 25+30x=60+20x | | 3x-6=0.5(2x-1+25) | | -7(2x+8)+4= | | x+x(0.13)=2476.67 | | (x+6)2=121 | | 4x-5+2x-10=5 | | 3x=2+4x-12 | | .94x+.44y=3.70 | | z+3=-6Z-4 | | -w=-2w+7 | | -8+8s=2s+10 | | 2y=x-16 | | 4x^2+19x-3=0 | | -2(3z+9)=24 | | -79-4x-8x=101 |